The Evaluation of Soil Fertility Status as the Basis to Increase Tree Growth in Roadside Greenery at Tegalega Sub Territories, Bandung - PURNAMA JATI (NIM : 11514012), RADITYA
Tegalega is one of the Sub Territories in the city of Bandung (SWK) with a very dense population (21,851 inhabitant (km2)-1). Currently, Tegalega has been designated as a mediapolis area, the centre of creative industry area. This condition increases the rate of infrastructure development and decreases the proportion of Green Open Space (RTH). The lack availability of urban land for the RTH makes the green pathway (JHJ) used as an alternative way to optimize the green space function. However, in general the trees in JHJ are not grown optimally. This study aims to determine the status of soil fertility for the purpose of increasing tree growth in the area of JHJ in SWK Tegalega. Zigzag systematic soil sampling with modifications was used in accordance to field conditions. This method based on the technical guidance of composite soil sampling from the 2011 Indonesian Agricultural Technology Assessment Institute. The sampling location was conducted in five selected roads, i.e Jl. Peta, Jl. Raya Kopo, Jl. Terusan Pasirkoja, Jl. Moch. Toha, and Jl. Soekarno Hatta with five sampling repetitions for each road. Soil analysis is used to determine soil fertility status refers to the 2015 Soil Fertility Criteria from the Soil Research Center. Five parameters used to determine fertility status such as cation exchange capacity, base saturation, soil organic carbon, total phosphorus and total potassium. The results show that the soil in JHJ SWK Tegalega has a cation exchange capacity around 18.82 - 26.85 cmol.kg-1, saturation base 119 - 156%, organic soil carbon 2.25 - 4.27%, total phosphorus 227.88 - 281.44 mg.100g-1, and total potassium 44.58 - 73.7 mg.100g-1. Based on the fertility status criteria from the Soil Research Center, lead to the conclusion that the status of the land on Jl. Peta has a high fertility, while the land on Jl. Raya Kopo, Jl. Terusan Pasirkoja, Jl. Moch. Toha, and Jl. Soekarno Hatta is moderate in category.